1993
DOI: 10.1111/j.1365-2710.1993.tb00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum creatinine levels during cardiac surgery: absence of effect by aminoglycosides

Abstract: The literature indicates that the relative nephrotoxicities of the three drugs used in this investigation are gentamicin > tobramycin > or = netilmicin. Serum creatinine levels over time were used in an attempt to elucidate the situation. They varied widely in all three groups and in controls in theatre. No definite trend was shown. Measurements performed for the ICU period showed continued variation. Fluctuations were so great during the perioperative period that the levels were analysed in terms of 44 mumol/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…29 Nevertheless, these increases were reversible and without sequelae. 29 Bertram and Summers 32 reported that the use of gentamicin did not measurably affect the kidney over the short period of treatment in patients undergoing cardiac surgery. Morin and colleagues, 33 in a study conducted in the rat, showed that gentamicin nephrotoxicity was potentiated by aprotinin.…”
Section: Vancomycin Gentamicin and The Kidneymentioning
confidence: 99%
“…29 Nevertheless, these increases were reversible and without sequelae. 29 Bertram and Summers 32 reported that the use of gentamicin did not measurably affect the kidney over the short period of treatment in patients undergoing cardiac surgery. Morin and colleagues, 33 in a study conducted in the rat, showed that gentamicin nephrotoxicity was potentiated by aprotinin.…”
Section: Vancomycin Gentamicin and The Kidneymentioning
confidence: 99%